Global supply chains, value added and production intensity: Case semiconductors - Harald Holmström; Martin Kenney; Timo O. Seppäläinen (The Research Institute of the Finnish Economy (ETLA), 2021)
Semiconductor chips and their production are foundational for future innovation, future developments of digitalization, and economic prosperity. However, the role of production when discussing who is creating and capturing value across different industrial supply chains has often been underestimated. In this report, we analyze the distribution of the value added in the semiconductor supply chain. Value added analysis is insufficient on its own to understand the importance of production; therefore, we also examine the share of operating profits that has been reinvested in the growth of tangible and intangible assets. Based on value added and reinvesting cycle analysis, we discuss production intensity, and we draw conclusion regarding how important production is for different supply chains and industries.
Keywords: L16; L22; L23; L63; 330; Semiconductor industry; Value chain; Value added; Value creation; Manufacturing; Tangible assets